Determinants of National Health Insurance Coverage for Family Planning Services Among Women in Indonesia - Nurmayunita, Heny; Asri, Yuni; Zakaria, Amin; Muhtar , Muhammad Solihuddin (Jurnal Jaminan Kesehatan Nasional, 2025)
Access to family planning services remains unequal in Indonesia despite the establishment of the National Health Insurance (NHI) program (Jaminan Kesehatan Nasional, JKN) to promote universal coverage. Disparities persist, particularly in contraceptive services, among women of reproductive age. This study examined the determinants of NHI coverage for contraceptive methods among Indonesian women of reproductive age. A cross-sectional analysis was conducted using data from 6,256 married or partnered women aged 15–49 years from the 2017 Indonesia Demographic and Health Survey (IDHS). Survey-weighted descriptive, bivariate, and multivariable logistic regression analyses were performed using Stata to identify the factors associated with NHI-covered contraceptive use. The results showed that Women with insurance schemes specifically covering family planning were significantly more likely to report contraceptive coverage through NHI (AOR: 47.5; 95% CI: 37.2–60.7). Secondary education (AOR: 2.08; 95% CI: 1.01–4.07) was positively associated with coverage, while rural residence (AOR: 0.71; 95% CI: 0.56–0.91), middle wealth status (AOR: 0.64; 95% CI: 0.46–0.88), and current employment (AOR: 0.79; 95% CI: 0.65–0.97) were negatively associated. These findings highlight persistent socioeconomic and geographic inequities in access to insured family planning services. Addressing these disparities requires targeted policy efforts, including automatic enrollment strategies for women in the informal sector, mobile registration units in rural areas, and public education campaigns to improve insurance literacy. Strengthening equitable access to family planning under the national insurance scheme is essential to achieving Indonesia’s reproductive health and universal coverage goals.